Nano-casting procedure for catalytic cobalt oxide bead preparation from calcium-alginate capsules: Activity in ammonia borane hydrolysis reaction - Kinsiz, Beyza Nur; Filiz, Bilge Coskuner; Depren, Serpil Kilic; Figen, Aysel Kanturk (ELSEVIER, 2021)
The preparation of bead type catalysts, which had a rapid and easy recoverable property for reusability and regeneration procedures during ammonia borane (NH3BH3) hydrolysis, was the main scope of this study. In the present study, the nano-casting procedure was adapted to cobalt oxide (Co3O4) microbeads preparation by multi-step ions exchange procedures. By nano-castings -, cobalt-alginate capsules provided the formation of a surface-active bead (140 +/- 0.4 mu m) in Co3O4 nanoparticles (25-35 nm) with enhanced performance for releasing of hydrogen from NH3BH3. Moreover, the catalysts used for 555 min without any mechanical damages during reusability tests and regeneration procedure. The bead type catalyst enabled the rapid and easy recover at the end of the reaction that improved the reuse of catalysts for the practical and curial for a commercial on-board hydrogen production application. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Cobalt-alginate; Capsules; Cobalt oxide; Bead; Ammonia borane; Hydrogen; HYDROGEN GENERATION; ADSORPTION CAPACITY; EFFICIENT CATALYSTS; OXYGEN VACANCIES; SIMPLE PYROLYSIS; DOPED CARBON; NANOPARTICLES; CO; EVOLUTION; COMPOSITE; Materials Science